Uncertainty: a neglected determinant of health behavior? - Berrigan, David; Dean, David; Senft Everson, Nicole; D’Angelo, Heather; Boyd, Patrick; Klein, William M. P.; Han, Paul K. J. (Frontiers in Psychology, 2023)
Health behaviors are critical determinants of the well-being of individuals and populations, and understanding the determinants of these behaviors has been a major focus of research. One important determinant that has received little direct attention in past health research is uncertainty: a complex phenomenon that pertains not only to scientific issues regarding the diagnosis, prognosis, prevention, and treatment of health problems, but also to personal issues regarding other important health-related concerns. Here, we make the case for greater attention to uncertainty in health behavior theory and research, and especially to personal uncertainties. We discuss three exemplary types of personal uncertainty—value uncertainty, capacity uncertainty, and motive uncertainty—which relate, respectively, to moral values, capacities to enact or change behaviors, and the motives and intentions of other persons or institutions. We argue that that personal uncertainties such as these influence health behaviors, but their influence has historically been obscured by a focus on other constructs such as self-efficacy and trust. Reconceptualizing and investigating health behavior as a problem of uncertainty can advance both our understanding of the determinants of healthy behaviors and our ability to promote them.